A Digital-Based Information System to Enhance Public Service Delivery in Samsat Services across Two Indonesian Provinces - Adelia Ramadani; Alyah Lestari Suherman; Nur Ilman (Poltanesa, 2025)
Samsat's digital transformation has greatly improved public service delivery in Indonesia, especially in South Sumatra and East Java.  Using a mixed-method approach that combines quantitative surveys and qualitative interviews, this study evaluates the effects of digitalization on administrative efficiency and user happiness.  Public trust in government agencies has increased, accessibility has improved, and service time has significantly decreased, according to the findings.    Persistent difficulties were found, nevertheless, such as poor rural infrastructure, low digital literacy, and problems synchronizing data among agencies.    In order to address these issues, this study suggests methods such as improving computer literacy initiatives, encouraging increased interagency cooperation, and designing user interfaces that are more inclusive. The research provides practical insights for optimizing digital public services, particularly in developing countries, and enriches the broader discourse on e-government implementation. The novelty of this study lies in its comparative analysis between two regional platforms, offering a comprehensive view of how administrative, technological, and socio-demographic factors influence digital service outcomes. The results contribute to informing policy strategies aimed at building more resilient, inclusive, and efficient public service systems in diverse governance contexts.